The effect of applying COSO-ERM model on reducing fraudulent financial reporting of commercial banks in Jordan - Abdul Aziz A. Abdul Rahman (Banks and Bank Systems, 2018)
This study aims to test the effect of applying the model of the Committee Sponsoring Organizations for enterprise risk management (COSO-ERM) on reducing fraudulent financial reporting in commercial banks operating in Jordan. Furthermore, the study identifies the role of each board of directors, audit committee, executive management, human resource management, and internal audit as one of the corporate governance mechanisms in enhancing the effectiveness of internal control systems. The study revealed an impact of applying the Committee of Sponsoring Organizations model for enterprise risk management (COSO-ERM) on preventing fraudulent financial reporting, where it reached influence around 77.8% on the dependent variable (fraudulent financial reporting). The study also found that each of internal control, event identification, risk assessment and response, and control activities variables affects dependent variable (fraudulent financial reporting) in commercial banks operating in Jordan.